2014
DOI: 10.1055/s-0034-1365285
|View full text |Cite
|
Sign up to set email alerts
|

Therapieadhärenz bei Asthma bronchiale – Versorgung unter Alltagsbedingungen in der pneumologischen Praxis

Abstract: In the present study, patients with asthma were interviewed with regard to their treatment adherence. It was shown that adherence is significantly influenced by age, occupation, quality of information about the disease and interest of the patient in disease, mode of action and use of the inhalation device. Younger, working patients who do not feel "completely adequately" informed are more likely to be not-adherent. Each aspect should be noted separately.The characterization enables forming target groups for ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…A recent study on whether patients with chronic bronchial asthma adhered to treatment also showed that adherence was significantly related to the quality of the information given to the patient. Nevertheless, the authors showed that in patients’ daily routines, only about 55% indicated feeling “totally sufficiently” informed about their medications’ mechanism of action [8]. Effective communication training methods for doctors-to-be are therefore needed.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study on whether patients with chronic bronchial asthma adhered to treatment also showed that adherence was significantly related to the quality of the information given to the patient. Nevertheless, the authors showed that in patients’ daily routines, only about 55% indicated feeling “totally sufficiently” informed about their medications’ mechanism of action [8]. Effective communication training methods for doctors-to-be are therefore needed.…”
Section: Introductionmentioning
confidence: 99%
“…Intensive Unterweisung im Gebrauch der Inhalatoren und Patientenschulung zu besserem Krankheitsverständnis tragen zusätzlich wesentlich zur Stabilität der Patienten bei [28]. Bei Wechsel des Inhalationssystems besteht zur Erzielung einer guten Adhärenz vor allem bei Patienten unter 50 Jahren, Berufstätigen und Patienten, die generell zu ihrer Erkrankung und der Wirkungsweise der Medikamente subjektiv zu wenig informiert sind, ein hoher Gesprächsbedarf [29]. Es ist zu empfehlen, mittels aut idem-Kennzeichnung die Abgabe desjenigen Inhalators durchzusetzen, auf den der Patient geschult ist, mit dem nach Lungenfunktion und Handhabung die beste Deposition zu erreichen ist, der eine gute Adhärenz erwarten lässt und der die geringste Treibhausgaswirkung entfaltet [30].…”
Section: Ausgehend Von Diesenunclassified